Transportation Process Of Container Goods From Container Freight Station To Container Yard at Port Of PT. Elang Sriwijaya Perkasa Palembang - Gabriel Ferdinand Sitompul; Meriah Kita Deliana; Fadiyah Hani Sabila (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Goods transportation is a medium and means of moving goods to their destination using the means of transport, and the unloading/unloading of the means of transport, whether carrying passengers or goods. The parties involved in transportation, one of which is sea cargo expedition (EMKL), is the business of handling documents and cargo that will be transported by ship or cargo that originates from ships that are transported and brought from the port container yard (CY) to the unloading warehouse/containeir freight station ( CFS) or carrying goods via container from the loading/freight container warehouse station (CFS) kei container yard (CY) port, PT. Elang Sriwijaya Perkasa Palembang is one of the companies that operates in the field of EIMKL (Sea Freight Transport Services) providing cargo transportation services, providing services for transporting goods via containers as well as loading and unloading. For this reason, the Sea Freight Shipping Company (EIMKL) is responsible for the safety of goods, delays in the arrival of goods, damage and loss of goods transported by trucks when they are transported out of the port container yard (CY), except for damage caused by the sender. on the item itself caused by several factors, whether weather, circumstances or when carrying out activities of stuffing or stripping goods into containers at the loading warehouse/containeir freight station (CFS). In this paper, the writing methods used are literature research and observational research at the source by carrying out activities in the field during field practice at PT. Elang Sriwijaya Perkasa Palembang and related agencies such as warehouses for loading stuffing goods, warehouses for unloading stripping goods, and container stacking yards/depots.